دور المنظار الليفي المرن في تشخيص آفات الحنجرة - إبراهيم مصطفى; الرستم محمد; غصن انشتاين (Latakia University Journal -Medical Sciences Series, 2019)
تكثر الشكايات المرضية الحنجرية عند عدد كبير من مراجعي العيادات الخارجية لاختصاص الأذن والأنف والحنجرة ،ويتطلب التشخيص المناسب لأسباب هذه الأعراض وسائل تشخيصية مناسبة، والمنظار الليفي المرن هو من أهم هذه الوسائل في تشخيص أمراض وآفاتها الحنجرة . لذا نهدف من خلال هذا البحث إلى دراسة دور هذه الوسيلة التشخيصية المهمة وبيان مدى قدرتها التشخيصية لآفات الحنجرة وسهولة الاستخدام وإمكانية توافرها ومقارنتها مع الوسائل الأخرى . تم فحص خمسين مريضا لديهم شكايات حنجرية مختلفة، أظهرت الدراسة فعالية دور المنظار الليفي المرن في الوصول إلى تشخيص صحيح وبشكل سهل للمريض . The laryngeal complaints are very common among a considerable number of patients who visit the ENT clinic. The correct diagnosis demands suitable diagnostic instruments and the flexible fiber optic laryngoscope is one of the most important diagnostic instruments for laryngeal diseases. In this study, we aim to examine the role of this important diagnostic instrument and to demonstrate its diagnostic benefit, practical use and to compare it with other devices. Fifty patients were tested for different laryngeal complaints and this study demonstrated the importance of flexible fiber optic laryngoscope in identifying the correct diagnosis easily.